Synthesis of Mn²⁺-doped CdS nanoparticles covered with different adsorptive layers and their application as biosensors - Fediv, V.I.; Rudko, G.Yu.; Savchuk, A.I.; Gule, E.G.; Davydenko, I.S.; Olar, O.I.; Volkov, K.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Colloidal CdS:Mn nanoparticles were synthesized in water solutions of the
polymer polyvinyl-pyrrolidone (PVP), the surfactant cetyl-trimethyl-ammonium bromide
(CTAB) and the mixture of PVP and CTAB. The sizes of nanoparticles were determined
by electron microscopy and optical absorption methods. The growth media influence on
photoluminescence of nanoparticles has been studied. It has been shown that the
chemical composition and structure of the adsorptive layer on the surface of
nanoparticles can be used as a technological tool to control their light emission. The
possibility to use CdS:Mn NPs grown in PVP as light-emitting labels in biological media
has been demonstrated.